Mental processes in teachers’ reflection papers: a transitivityanalysis in systemic functional linguistics - Munalim, Leonardo Orevillo (Penerbit Universiti Kebangsaan Malaysia, 2017)
The tradition of reflective teaching has been around for thirty-four years since Schӧn (1983) first proposed the notion of reflective practice. Many studies heavily rely on written genres in the investigation of teachers’ reflective practices. Thematic categories were threshed out through content and descriptive analyses. However, these themes were not culled from the clauses of mental processes employed by the teachers to express their inner world of experiences. This exploratory study proposed the transitivity model in Systemic Functional Linguistics (SFL) to generate the mental processes from reflection papers. Initial papers with 17,937 word tokens were produced by 28 teachers of English enrolled in a writing course. All processes were generated by UAM Corpus Tool. The themes generated from the Phenomena felt, thought of, sensed, desired, and perceived by the Senser were culled using content analysis. Results show that teachers are still boxed within the default material and relational processes. Results demonstrate that they employed higher mental types of sensing such as cognitive and desiderative. Based on the Phenomena, the top themes include: (1) commendations for the course professor, (2) writing process, its challenges, nature, and concepts, and (3) actual classroom experiences, learnings, and the subject. Although the results corroborate with the themes identified in previous studies, these present themes may be treated as valid and more realistic views and dimensions of reflective practices. This exploratory study suggests that the Phenomenon in the mental processes may be an ideal situs of looking into teachers’ human internal affairs as reflective practitioners.